Hubungan Kualitas Informasi Aplikasi Goodreads dengan Penentuan Preferensi Buku pada Bibliofilia - Yasyfi Saffanah, Aliyah; Rusmana, Agus; Anwar, Rully Khairul (Literatify: Trends in Library Developments, 2025)
The digital era has prompted online sites to provide an information that aligns with users’ needs. Information accessibility could help bibliophiles in order to retrieve an information and decide on their book preferences effectively and efficiently. This research aims to analyze the correlation between Goodreads’ information quality and bibliophiles’ book preference. Information quality is measured through three (3) indicators: accuracy, timeliness, and relevancy. This research employed a quantitative method through a survey. The sampling method used was simple random sampling due to the homogency of the population. The population consisted of X @basebuku followers whom using Goodreads, in which 230 people, and 70 people were selected. The results, analyzed using Spearman’s Rank Correlation, indicate a moderate correlation between information quality and book preferences. Furthermore, each indicators indicate a correlation with book preferences, yet there’s difference on the strength of correlation. Accuracy and book preferences indicate a weak correlation; timeliness and book preferences indicate a moderate correlation; relevancy and book preferences indicate a strong correlation.